The stability of interest as measured by the PGPII-M and its correlates : its congruence to selected courses and motivational factors - Mina, Wilfredo B. (Animo Repository, 1978)
In this study, the descriptive-normative survey was used as a method. One hundred seventy-eight (178) of the 313 freshmen of Saint Louis University (SLU) of school year 1973-1974 who had complete interest test results (first year and third year interest test results) were made the subjects of the first part of the study which is the stability of interests. Ninety-two (92) students out of the 178 who were then enrolled at SLU during the first semester of school year 1977-1978 were made the respondents to the questionnaire prepared for determining the congruence of interest with course choices which comprised the second part of the study. The Philpsycor-Geist Picture Interest Inventory Test for Male-Philippine Edition was used to bring out the interest of the respondents for the first test and retest. PGPII-M is a test adaptation of the Geist Picture Interest Inventory. It was adopted by Estefania Aldaba-Lim. A questionnaire, purported to identify the course choice and motivational forces which influence the students in their course choice, was used to supplement the gathering of data. In seeking to determine whether inventoried interest among the high school male students were consistent and stable over a period of two (2) years, a slight difference between the respondents with stable interest and respondents with unstable interest was observed through simple inspection of the data. However, when statistical analysis was performed, no significant difference was found. Hence, it was concluded that the inventoried interest in the first year of the subjects under study were not significantly related to the inventoried interest of the same subjects in the third year. This indicated therefore that interest is not definitely stable over a period of two years. Secondly, the study indicated that factors such as age, IQ, father's occupation and ordinal position were not related to the stability of the interest. However, through simple inspection of the data, it showed that there were slight differences from each of these